Expression of Cysteine-Rich Secreted Acidic Protein in Multiple Myeloma and Its Effect on the Biological Behavior of Cancer Cells - Qiqun Pan (Hindawi Limited, 2021)
The multiple myeloma is a malignant clonal tumor of bone marrow plasma cells that is incurable and inevitably recurrent. The mechanisms of progression include tumor cell metastasis, immune escape, resistance to apoptosis, and malignant proliferation. The cysteine-rich secreted acidic protein is closely related to the growth, development, remodeling, and repair of cells and tissues. In our study, we divided myeloma patients and patients with other blood diseases into groups and measured the cysteine-rich secreted acidic protein (SPARC) content in the serum of different groups of patients as well as the prognostic differences. The U266 cells were transfected with interfering vectors and overexpressed SPARC vectors to determine the physiological functions of MM cells. Our results showed that SPARC was highly expressed in MM and the survival rate of the high SPARC expression group was lower than that of the low expression group. Interfering SPARC vectors inhibited cancer cell proliferation, migration, and invasion and promoted apoptosis. Overexpression of SPARC vectors promoted cancer cell development. SPARC affected the patient’s disease development by regulating the biological behavior of the MM cells.